2011
DOI: 10.1523/jneurosci.6604-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Youth at Risk for Obesity Show Greater Activation of Striatal and Somatosensory Regions to Food

Abstract: Obese versus normal-weight humans have less striatal D2 receptors and striatal response to food intake, and weaker striatal response to food predicts weight gain for individuals at genetic risk for reduced dopamine (DA) signaling, consistent with the reward deficit theory of obesity. Yet these may not be initial vulnerability factors, as overeating reduces D2 receptor density, D2 sensitivity, reward sensitivity, and striatal response to food. Obese versus normal-weight humans also show greater striatal, amygda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
289
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(315 citation statements)
references
References 39 publications
(59 reference statements)
17
289
2
Order By: Relevance
“…We also found that RYGB decreased the CNS responses in the insula in response to chocolate milk consumption, which was accompanied by weight reduction. At first sight, this finding may be considered to be at odds with previous studies, as several (4,17), but not all (31,32), previous studies demonstrated that leaner individuals have increased responsivity to the consumption of chocolate milk in comparison with obese individuals. However, in general, both lean and obese individuals are presumed to "like" the palatable gustatory food cue but seem to differ in the central responses and process of the reward evaluation of this cue.…”
Section: Resultsmentioning
confidence: 71%
“…We also found that RYGB decreased the CNS responses in the insula in response to chocolate milk consumption, which was accompanied by weight reduction. At first sight, this finding may be considered to be at odds with previous studies, as several (4,17), but not all (31,32), previous studies demonstrated that leaner individuals have increased responsivity to the consumption of chocolate milk in comparison with obese individuals. However, in general, both lean and obese individuals are presumed to "like" the palatable gustatory food cue but seem to differ in the central responses and process of the reward evaluation of this cue.…”
Section: Resultsmentioning
confidence: 71%
“…Obese women showed greater response to immediate reward (even in the face of delayed negative consequences) as opposed to lean women, and this differential response was not observed in obese men. 53 Another important imaging study demonstrated that youth who are at risk for obesity (defined as having both parents overweight/obese) showed an increased activation of the reward circuitry in response to food or monetary rewards, 54 suggesting that parental obesity can contribute to the child's risk for obesity. This same research group has also shown that reduced responding of the striatum to palatable food consumption can develop with weight gain, as opposed to existing prior to weight gain.…”
Section: Postnatal Effects Of a High-fat Dietmentioning
confidence: 99%
“…Disturbed sensitivity to rewards is also found in children with obesity. Research showed that compared to average weight, obese children exhibit a hyperresponsivity to reward (Stice, Yokum, Burger, Epstein, & Small, 2011;Van den Berg et al, 2011;Verbeken, Braet, Lammertyn, Moens, & Goossens, 2012) and prefer immediate over delayed gratification (Verbeken, Braet, & Lammertyn, in prep). A feature that may increase children's motivation is adding computer game-elements to tasks.…”
mentioning
confidence: 99%